Occurrence of the chinese mitten crab Eriocheir sinensis (H. Milne Edwards) in South Iraq - Hashim, A.A. (Mesopotamian Journal of Marine Sciences, 2022)
The distribution of the invasive Chinese mitten crab Eriocheir sinensis in Shatt Al-Basrah Canal and Shatt Al-Arab River was investigated. The earlier published record of this species was in 2006 where only a single specimen was obtained from Shatt Al-Basrah Canal, but the species has long been observed in the region. The present work monitored the recent occurrence of the species where living and non living specimens were captured in large numbers. Although the species migrate to the sea for reproduction, it was not yet recorded from the North West Arabian Gulf region. Detailed description of the captured crabs is provided. Carapace width ranged from 53.4 to 56.6 mm and carapace length ranged from 56 to 62.4 mm. Recent rise in salinity or the change in water chemistry of south Iraq may play vital role in increasing the population of the mitten crab.